Sensitivity of Molds From Spoiled Dairy Products Towards Bioprotective Lactic Acid Bacteria Cultures - Shi, Ce; Knøchel, Susanne (Frontiers in Microbiology, 2021)
Fungal spoilage of dairy products is a major concern due to food waste and economical losses, some fungal metabolites may furthermore have adverse effects on human health. The use of lactic acid bacteria (LAB) is emerging as a potential clean label alternative to chemical preservatives. Here, our aim was to characterize the growth potential at three storage temperatures (5, 16, and 25°C) of a panel of molds (four Mucor and nine Penicillium strains) isolated from dairy products, then investigate the susceptibility of the molds toward 12 LAB cultures. Fungal cell growth and morphology in malt extract broth was monitored using oCelloScope at 25°C for 24 h. Mucor plumbeus 01180036 was the fastest growing and Penicillium roqueforti ISI4 (P. roqueforti ISI4) the slowest of the tested molds. On yogurt-agar plates, all molds grew at 5, 16, and 25°C in a temperature-dependent manner with Mucor strains growing faster than Penicillium strains regardless of temperature. The sensitivity toward 12 LAB cultures was tested using high-throughput overlay method and here all the molds except P. roqueforti ISI4 were strongly inhibited. The antifungal action of these LAB was confirmed when spotting mold spores on agar plates containing live cells of the LAB strains. However, if cells were removed from the fermentates, the inhibitory effects decreased markedly. The antifungal effects of volatiles tested in a plate-on-plate system without direct contact between mold and LAB culture media were modest. Some LAB binary combinations improved the antifungal activity against the growth of several molds beyond that of single cultures in yogurt serum. The role of competitive exclusion due to manganese depletion was examined as a possible antifungal mechanism for six Penicillium and two Mucor strains. It was shown that this mechanism was a major inhibition factor for the molds tested apart from the non-inhibited P. roqueforti ISI4 since addition of manganese with increasing concentrations of up to 0.1 mM resulted in partly or fully restored mold growth in yogurt. These findings help to understand the parameters influencing the mold spoilage of dairy products and the interactions between the contaminating strains, substrate, and bioprotective LAB cultures.